2019
DOI: 10.1016/j.adaj.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Is it time US dentistry ended its opioid dependence?

Abstract: This is a repository copy of Is it time US dentistry ended its opioid dependence?.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…treatment and, when necessary, the prescription of medicines. 2,3 Nonsteroidal anti-inflammatory drugs (NSAID), opioids, and analgesics are frequently prescribed by dental practitioners. 3,4,5 Research shows an overall increase in the prescription of medicines to control pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…treatment and, when necessary, the prescription of medicines. 2,3 Nonsteroidal anti-inflammatory drugs (NSAID), opioids, and analgesics are frequently prescribed by dental practitioners. 3,4,5 Research shows an overall increase in the prescription of medicines to control pain.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Nonsteroidal anti-inflammatory drugs (NSAID), opioids, and analgesics are frequently prescribed by dental practitioners. 3,4,5 Research shows an overall increase in the prescription of medicines to control pain. 6,7,8 It is recognized that millions of people suffer from untreated pain around the world.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of solid pain and biopsychosocial training may also impede the comprehensive assessment of initiating and perpetuating factors contributing to the pain presentation, leading to a mechanistic, reductionist approach that can be ineffective, inhumane, and potentially harmful. Additionally, this knowledge is key to appropriate risk assessment (e.g., potential for addiction, intake of benzodiazepines, presence of sleep apnea) prior to prescribing opioid medications for acute pain relief after a dental procedure, which could lead to potential deleterious outcomes such as respiratory depression, abuse, misuse, dependence, and overdose 42 . Dentist should know that opioids are generally not indicated for nonmalignant OFP, and its avoidance when possible is warranted in the short and long term 42,43 .…”
Section: Barriers To Ofp Education and Evidence‐based Practicementioning
confidence: 99%
“…Additionally, this knowledge is key to appropriate risk assessment (e.g., potential for addiction, intake of benzodiazepines, presence of sleep apnea) prior to prescribing opioid medications for acute pain relief after a dental procedure, which could lead to potential deleterious outcomes such as respiratory depression, abuse, misuse, dependence, and overdose 42 . Dentist should know that opioids are generally not indicated for nonmalignant OFP, and its avoidance when possible is warranted in the short and long term 42,43 . Thus, there is great need for a coordinated effort from international experts in the field to keep OFP educational standards up to date with the best available evidence in dental schools worldwide, while facilitating collaboration with other dental, medical, and health specialties 36 …”
Section: Barriers To Ofp Education and Evidence‐based Practicementioning
confidence: 99%
“…Opioid misuse and harms are a public health issue in Australia, where opioids for nonmedical use are predominately sourced through social networks 15 . It has been shown that dentists tend to prescribe opioids unnecessarily and for longer than required 16–18 . A cohort analysis showed that a substantial proportion of young adults are exposed to opioid use through dentists, and this may subsequently lead to opioid abuse 19 …”
Section: Introductionmentioning
confidence: 99%